The effect of rotating magnetic turbulators on the convective heat transfer and pressure drop through a circular tube: Experimental investigation - Seyyed Morteza Mansouri; Mohamad Ali Bijarchi; L Siamak K Kazemzadeh Hannani (International Journal of Thermofluids)
In this study, forced convective heat transfer inside a tube is investigated by introducing a novel active method that uses an external rotational magnetic field to rotate magnetic spheres in a tube under constant heat flux. To generate the rotating magnetic field, an electric signal generator with adjustable frequencies is used along with a Rodin star coil. The rotation of the magnetic spheres on the inner surface of the tube and simultaneously around themselves disrupts the hydraulic and thermal boundary layers. Hence, the flow regime shifts from laminar to turbulent, leading to an increase in both convective heat transfer and pressure drop inside the tube, which are respectively, favorable and undesirable impacts. The effect of the location and number of the rotating and non-rotating spheres, as well as their presence and absence, and their rotation direction relative to each other on the local and average Nusselt numbers, friction coefficient, and thermal performance factor is studied. Results show that the existence of the rotating magnetic spheres leads to a remarkable elevation in the local Nusselt number after the sphere. Hence, the average Nusselt number is increased significantly in the case of rotating spheres compared to the simple tube. By increasing the number of rotating spheres, locating the rotating spheres closer to the upstream, or rotating the spheres opposite to each other, the average Nusselt number increases, while the enhancement of friction coefficient is negligible. Hence the thermal performance factor elevates up to 24% compared to a simple tube.